2014
DOI: 10.1016/j.ajpath.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

HCV Infection Selectively Impairs Type I but Not Type III IFN Signaling

Abstract: A stable and persistent Hepatitis C virus (HCV) replication cell culture model was developed to examine clearance of viral replication during long-term treatment using interferon-α (IFN-α), IFN-λ, and ribavirin (RBV). Persistently HCV-infected cell culture exhibited an impaired antiviral response to IFN-α+RBV combination treatment, whereas IFN-λ treatment produced a strong and sustained antiviral response that cleared HCV replication. HCV replication in persistently infected cells induced chronic endoplasmic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 41 publications
4
84
0
Order By: Relevance
“…Accumulation of large amounts of viral proteins during persistent replication induces a stress response in infected PHHs. Prior studies have shown that the UPR was either partially activated or suppressed to attenuate ER‐stress‐mediated hepatocellular apoptosis using transformed hepatoma cells (Huh‐7.5) soon after virus infection 9, 10. It is unclear whether persistent HCV replication induced chronic or adaptive ER stress in untransformed hepatocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of large amounts of viral proteins during persistent replication induces a stress response in infected PHHs. Prior studies have shown that the UPR was either partially activated or suppressed to attenuate ER‐stress‐mediated hepatocellular apoptosis using transformed hepatoma cells (Huh‐7.5) soon after virus infection 9, 10. It is unclear whether persistent HCV replication induced chronic or adaptive ER stress in untransformed hepatocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past several years, many investigators, including our own, showed that HCV‐associated ER stress induced an autophagy response, which results in impaired host innate immunity through blocking endogenous IFN production7, 9 and also escapes from exogenously added IFN‐α and ribavirin (RBV)‐based antiviral therapy through degradation of interferon‐alpha receptor 1 and RBV transporter 10, 11. In this report, we found that HCV infection induces chaperone‐mediated autophagy (CMA) as a cell survival mechanism to avoid the ER‐stress response.…”
Section: Introductionmentioning
confidence: 99%
“…The IL28B gene locus encodes for IFN-3, a member of type III IFN family (Chandra et al, 2014). Many studies have demonstrated that the presence of a single nucleotide polymorphism (SNP) at the IL28B locus is associated with a reduced response to Peg IFN/RBV therapy and also an increased prevalence of PBMC infection (Amanzada et al, 2011;Youssef et al, 2013).…”
Section: Potential Pathogenic Mechanisms Resulting In An Ocimentioning
confidence: 99%
“…The Renilla luciferase reporter-based pJFH-⌬V3-Rluc clone used in our experiment was described previously (22) Interferon and RBV treatment and HCV quantification. To study the mechanisms of HCV clearance by RBV, we established a stable and persistently HCV-infected cell culture system with Huh-7.5 cells that releases infectious virus particles and enables quantification of HCV replication by the measurement of Renilla luciferase, Western blotting, and immunostaining (20). RBV treatment of HCV-infected cultures was performed in six-well tissue culture plates (Costar; Corning, Tewksbury, MA) in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we reported that a combined HCV-induced endoplasmic reticulum (ER) stress and autophagy response downregulates the expression of IFN-␣ receptor 1, which is why HCV replication in a persistently infected cell culture is not completely inhibited by IFN-␣ (20,21). In this study, we investigated virus and host cell interactions that impair RBV antiviral activity in a persistently HCV-infected cell culture system.…”
mentioning
confidence: 99%